Experimental and Analytical Investigation of Classic Spar Responses - Ng , C.Y. (2010)
Abstract - This paper presents the results of model tests of an offshore classic spar platform subjected to regular sea waves that was conducted in the wave tank of the offshore engineering laboratory at Universiti Teknologi PETRONAS. The measured responses were compared with the numerical results obtained by using Morison equation and linear diffraction method. The classic spar was modeled as a rigid body with three degrees of freedom restrained by mooring lines. Linear Airy wave theory and Morison modified equation were used for calculating the wave forces on the structure in the first case. The mass, damping and stiffness matrices were evaluated at every time step and the equations of motion were formulated for the platform dynamic equilibrium. The equations were solved using Newmark Beta time domain dynamic analysis method. The results were obtained as transfer functions in surge, heave and pitch. In the second case, the transfer functions were obtained using software based on linear diffraction method. The experimental responses were compared with the analytical responses and found in good agreement.